2013
DOI: 10.1159/000351587
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin α<sub>1</sub> Activates Complement Receptor-Mediated Phagocytosis in Human Monocyte-Derived Macrophages

Abstract: Thymosin α1 (Tα1) is a naturally occurring thymic peptide used worldwide in clinical trials for the treatment of infectious diseases and cancer. The immunomodulatory activity of Tα1 on innate immunity effector cells has been extensively described, but its mechanism of action is not completely understood. We report that Tα1-exposed human monocyte-derived macrophages (MDMs) assume the typical activated morphology also exhibited by lipopolysaccharide-activated MDMs, but show a comparatively higher abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 35 publications
(50 reference statements)
2
13
0
Order By: Relevance
“…These findings are in agreement with a growing body of evidence attesting the pleiotropy of this hormone peptide, which targets both normal and tumor cells interacting with multiple cellular components [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]; as such, they have generated a renewed interest. Studies of the serum Tα1 levels and of its interaction with soluble proteins [ 23 , 29 ] have also raised questions about the transport and localization of Tα1 in tissues and of the dynamics underlying the biological effects of this peptide in different clinical situations.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings are in agreement with a growing body of evidence attesting the pleiotropy of this hormone peptide, which targets both normal and tumor cells interacting with multiple cellular components [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]; as such, they have generated a renewed interest. Studies of the serum Tα1 levels and of its interaction with soluble proteins [ 23 , 29 ] have also raised questions about the transport and localization of Tα1 in tissues and of the dynamics underlying the biological effects of this peptide in different clinical situations.…”
Section: Introductionsupporting
confidence: 85%
“…A univocal mechanism of action of Tα1 is still unknown since no specific receptors for Tα1 have been identified. Tα1 induces T-cell and dendritic cell (DC) maturation and interleukin (IL)-2 expression; it is also capable of upregulating the expression of some Toll-like receptors (TLRs) in murine DCs protecting mice from invasive aspergillosis in the MyD88 (myeloid differentiate factor 88)-dependent way [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Tα1 activates a protein kinase C (PKC)-IκB kinase (TRAF6) that is an atypical signaling pathway activating nuclear factor-κB and initiating the cytokine gene expression in murine bone marrow-derived macrophages [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages can regulate inflammation, but a janitorial function is also important, for example, the removal of apoptotic cells (efferocytosis) [9][10][11] . In this context, autophagy, involving the recycling of cells and debris, plays a critical role [12][13][14][15] .…”
Section: Foodies Of Innate Immunitymentioning
confidence: 99%
“…It will be interesting to see whether this finding has clinical implications. For instance, Annalucia Serafino and colleagues recently reported that thymosin α 1 can boost complement receptor-mediated phagocytosis by activating a TRAF6-atypical protein kinase C-IκB kinase signaling pathway [18]. Notably, many of these signaling events involve an activation of Pyk kinases.…”
mentioning
confidence: 99%